KOMBINASI AIR KELAPA DAN EKSTRAK TOMAT PADA MEDIA GROWMORE UNTUK SUBKULTUR ANGGREK Dendrobium candy strip lasianthera (CL) - Ade Putri; Rita Ningsih; Sri Ambardini (Universitas Lambung Mangkurat, 2026)
This study aims to determine the effects of individual and combined concentrations of coconut water and tomato extract as natural plant growth regulators (PGRs) on the in vitro growth of Dendrobium candy strip lasianthera (CL) plantlets cultured on Growmore subculture medium. Shoot explants originating from sterile cultures were selected, with an approximate size of 0.5 cm. The experiment employed a completely randomized design (CRD) with a two-factor treatment: tomato extract (T) concentration consisting of four levels (0, 10, 20, and 30%) and coconut water (K) at four levels (0, 50, 75, and 100 mL/L), each with five replications. Observations were conducted over an 8-week period. Data were analyzed using a Two-Way Analysis of Variance (ANOVA) followed by Duncan’s Multiple Range Test (DMRT) at a 5% significance level. The results indicated that the single treatment of tomato extract significantly affected the number of leaves and shoots. The single treatment of coconut water had a significant effect on the number of roots. Furthermore, the combination of coconut water and tomato extract significantly influenced plantlet height and shoot length. The optimal single tomato extract treatments were 30% (T3), producing an average of 3.8 leaves, and 10% (T1), producing an average of 2.6 shoots. The most effective single coconut water treatment was 100 mL/L (K3), which produced an average of 3.05 roots. The most effective combination treatments were 100 mL/L coconut water with 30% tomato extract (K3T3), resulting in a plantlet height of 1.36 cm, and 50 mL/L coconut water with 30% tomato extract (K1T3), resulting in a shoot length of 1.2 mm.